Estimating residential water demand in southern Africa - Jacobs, H E; Geustyn, L C; Loubser, B F; van der Merwe, B (Journal of the South African Institution of Civil Engineers, 2004)
It is understandable that an easy method to obtain estimates of residential water demand is often used. These estimates are also extended to calculate peak demand and sewer flow, and impact an authority's water and sewer infrastructure budget and finally its expenditure. Guideline curves are presented in this paper that can be used to estimate annual average residential water demand based on stand size. The measured water consumption and stand size of more than 600 000 single residential stands were obtained. Treasury databases for Cape Town, Ekurhuleni, George, Midrand, Randfontein and Tshwane were analysed in detail and the results compared to similar work in Windhoek. The large number of records made it possible to conduct statistical analyses and to investigate the distribution of data for stand size intervals of 100 m super(2). The water demand of similar sized stands in townships and suburbs could be compared. A strong relationship exists between the average annual water demand and stand size. The authors note that a model based on stand size has limited application only when better methods are not available.